Assessing the influence of oil and grease and salt content on fish canning wastewater biodegradation through respirometric tests - Cristovão, Raquel (2018)
Fish canning industry wastewaters have high organic matter, oil and grease and salt (NaCl) content, which make difficult a proper treatment before discharge. In this work, their treatment was evaluated via activated sludge aerobic biological process through respirometric tests. Inhibition was found to be significant for NaCl concentr ations higher than 17.5 g/L. On the other hand, the oil and grease content affects the wastewater biodegradability in the same way that the organic matter content expressed as chemical oxygen demand: the lower oil and grease and organic matter concentrations, the lower the percentage of wastewater biodegradability. As a final conclusion, the aerobic biological treatment process by activated sludge proved to be appropriate to treat fish canning industrial wastewaters, leading to high organic matter degradation rates (average value of 4900 mg O2 /g COD .d). Additionally, the experimental results achieved with the respirometric tests may be useful for the design of activated sludge plants to treat this type of wastewaters.